Experimental Plastic Reactivation of Pseudotachylyte‐Filled Shear Zones. Issue 5 (6th March 2021) - Passelègue, François X.; Tielke, Jacob; Mecklenburgh, Julian; Violay, Marie; Deldicque, Damien; Di Toro, Giulio
Abstract: Pseudotachylytes are fine‐grained fault rocks that solidify from melt that is produced in fault zones during earthquakes. Exposed sections of natural fault zones reveal evidence of postseismic plastic deformation (i.e., reactivation) of pseudotachylyte, which suggests these rocks may contribute to aseismic slip behavior in regions of repeated seismicity. To measure the plastic flow behavior of pseudotachylyte, we performed high‐temperature deformation experiments on pseudotachylyte from the Gole Larghe Fault Zone, Italy. Plastic reactivation of pseudotachylyte occurs at temperatures above 700°C for strain rates accessible during laboratory experiments. Extrapolation of experimental results to natural conditions demonstrates that pseudotachylyte deforms via diffusion creep at crustal conditions and is much weaker than host rocks in seismically active regions. Importantly, the presence of plastically deforming pseudotachylyte may influence the thickness of the seismogenic layer in some fault zones that experience repeated seismicity. Plain Language Summary: While the plastic strength of individual minerals constituting the continental crust are well known, the plastic strength of rocks resulting from coseismic slip in seismically active regions has yet to be measured, despite of the observations of their plastic reactivation. Here, we establish the flow law parameters controlling the strength of natural pseudotachylyte, fine‐grained fault rocks that crystalize from melt produced in fault zones during earthquakes. Experiments where conducted at temperature ranging from 700 to 900°C and at a confining pressure of 300 MPa. Our experimental results demonstrate that pseudotachylyte deforms via diffusion creep at crustal conditions. Flow law parameters derived from plastically deforming pseudotachylyte suggest that the presence of pseudotachylyte along faults drastically reduces the strength of the seismically active continental crust. Finally, the presence of seismically generated pseudotachylyte is likely to strongly influence the thickness of the seismogenic layer, since seismicity is rare in mature crustal faults at depths below which pseudotachylyte deforms plastically. Key Points: Natural pseudotachylyte‐filled shear zones can reactivate plastically at high temperature Plastic deformation processes are dominated by diffusion creep at low temperatures Rheology of pseudotachylytes can reduce the strength of the continental crust